Risk of pulmonary tuberculosis transmission among household contacts - Rahmawati, Eri; Nurhayati, Etiek; Sutriswanto, Sutriswanto (ELECTRON (Journal of Science and Technology), 2025)
Tuberculosis is an infectious disease caused by the Mycobacterium tuberculosis bacillus. Pulmonary TB disease is transmitted through the air (droplet nuclei), when the patient coughs, sneezes, or talks, pulmonary TB germs in the form of droplets will be scattered in the air. Household contact with active tuberculosis people has higher risk of being infected compared to those who are not in contact. This study aims to determine the risk of pulmonary TB transmission in people who are in house contact, including length of contact and sleeping in the same room, in the working area of Puskesmas Perumnas II, West Pontianak District. This research is categorized as descriptive analytic with total sampling technique. The sample size was 77 respondents who lived in the same house with pulmonary TB patients who were still actively seeking treatment in the working area of Perumnas II Community Health Center. Sample criteria included inclusion and exclusion criteria. The research was conducted through direct interviews using questionnaires, observation sheets, and microscopic BTA data collection. The results showed that out of 77 respondents, 37 respondents (48.1%) had contact with patients ≥ 8 hours and 4 of them were BTA positive. The prevalence of transmission based on length of contact was 10.8% and based on sleeping in the same room was 36.3%. The study concluded that there was a prevalence of pulmonary TB transmission in people who were in contact with the patient.